Conformational proofreading of distant 40S ribosomal subunit maturation events by a long-range communication mechanism - Mitterer, Valentin; Shayan, Ramtin; Ferreira-Cerca, Sébastien; Murat, Guillaume; Enne, Tanja; Rinaldi, Dana; Weigl, Sarah; Omanic, Hajrija; Gleizes, Pierre-Emmanuel; Kressler, Dieter; Plisson-Chastang, Celia; Pertschy, Brigitte (Nature Communications, 2019)
Eukaryotic ribosomes are synthesized in a hierarchical process driven by a plethora of assembly factors, but how maturation events at physically distant sites on pre-ribosomes are coordinated is poorly understood. Using functional analyses and cryo-EM, we show that ribosomal protein Rps20 orchestrates communication between two multi-step maturation events across the pre-40S subunit. Our study reveals that during pre-40S maturation, formation of essential contacts between Rps20 and Rps3 permits assembly factor Ltv1 to recruit the Hrr25 kinase, thereby promoting Ltv1 phosphorylation. In parallel, a deeply buried Rps20 loop reaches to the opposite pre-40S side, where it stimulates Rio2 ATPase activity. Both cascades converge to the final maturation steps releasing Rio2 and phosphorylated Ltv1. We propose that conformational proofreading exerted via Rps20 constitutes a checkpoint permitting assembly factor release and progression of pre-40S maturation only after completion of all earlier maturation steps.